Ruminative and mood associations for age differences in social and directive reasons to think and talk about life experiences. - Jorge J Ricarte; Laura Ros; Jose M Latorre; Tom J Barry (PLoS ONE)
Reminiscing, or thinking and talking about our past experiences, can have mood enhancing effects. Rumination is implicated in reminiscence and yet has been shown to have negative effects on mood, with important differences between age groups. However, age differences in the effects of reminiscing on mood, and particularly the effects of rumination within reminiscence, are less explored. Two different age groups completed self-report measures of the positive directive (planning for present and future behaviors) and social (communication) uses of autobiographical memory, as well as maladaptive rumination and depression symptom severity. Young participants (Mean age: 21.82) ruminated more and reported greater frequency of using the directive and social functions of thinking and talking about past experiences than older adults (Mean age: 71.82). These reminiscence processes were also differentially associated with depression symptoms between age groups when tested in structural equation models. In older participants, but not young participants, the directive function was negatively associated with depression severity; in young participants, but not old participants, the social function was negatively associated with depression severity. Furthermore, although depressive and abstract rumination was directly positively related to depression scores in both samples, this association was inverted when the effect of rumination on depression was calculated through functions of reminiscence. The implications of these results for intervention development in older versus young adults, is discussed.